Evaluation of offshore marine current energy performance in Malaysia - Zahari, S.H. (Institute of Physics Publishing, 2020)
Venturi Marine Current Energy Device (VMCED) is a current energy converter, which is focused in this research that aimed to harness the continuous movement of ocean current. It focuses on the venture effect to increase the efficiency of the flow velocity in resulting higher output energy from the ocean current. This research aimed to identify the best potential location of Malaysian waters to deploy the device. A computational fluid dynamic analysis was conducted in this study considering two important parameters i.e. velocity and differential pressure in the VMCED. These parameters were adopted in the analysis to measure the highest velocity and pressure differential. Among of the locations in Malaysia analysed in this study, it is to conclude that VMCED is best to be deployed in Straits of Malacca. This location measured the highest velocity and differential pressure of ocean current compared to others. Â© Published under licence by IOP Publishing Ltd.